The phytochemical contents and antimicrobial activities of Malaysian Calophyllum rubiginosum - ALkhamaiseh, Suhaib Ibrahim; Bakhtiar, M. Taher; Ahmad, Farediah (Science Publications, 2011)
Problem statement: Many species of plants in Malaysia are widely used in folk medicine. However, Calophyllum species have been used in traditional medicine for their therapeutic values for many years. Several studies reported that antimicrobial, antifungal, anti-HIV and anti-cancer compounds were isolated from numerous Calophyllum species. Approach: The stem bark was extracted by EtOH, after with it was fractionated with n-Hexane, Dichloromethane (DCM) and MeOH by using vacuum liquid chromatography apparatus. Phytochemical contents were examined to evaluate the phinolic, flavonoid and flavonol contents. Also the antimicrobial activity was carried out by using disc diffusion and dilution method to evaluate antimicrobial activity of the crude and the fractions respectively. Six references microbial strains of human pathogens were used for examined the anti microbial activity. The two Gram-positive bacteria (Staphylococcus aureus, Bacillus cereus) and two Gram-negative (Pseudomonas aeruginosa, Escherichia coli) were used for antibacterial test. Also two fungal strains (Candida albicans and Cryptococcus neoformans) were used for antifungal test. Results: Although the C. rubiginosum has phytochemicals as all plants, but it was showed a high content of flavonol in the range of 11.9- 15.2 μg mL−1. The C. rubiginosum fractions were showed no activity against gram negative and fungus. However, the non polar and semi polar fractions were showed a result MIC 12.5 μg mL−1 against B.cereus bacteria. While the MeOH fraction indicated for low or no activity against bacteria and fungus. Conclusion: At last, the optimistic result of this study encourage us to go forward for further studies in the future to isolate the active compound of the stem bark of C. rubiginosum, where it could lead to a new antibiotic, whereas this species never investigated before.